2012
DOI: 10.1111/j.1753-4887.2012.00518.x
|View full text |Cite
|
Sign up to set email alerts
|

Does food marketing need to make us fat? A review and solutions

Abstract: Food marketing is often singled out as the leading cause of the obesity epidemic. The present review examines current food marketing practices to determine how exactly they may be influencing food intake, and how food marketers could meet their business objectives while helping people eat healthier. Particular attention is paid to the insights provided by recently published studies in the areas of marketing and consumer research, and those insights are integrated with findings from studies in nutrition and rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
278
2
21

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 354 publications
(313 citation statements)
references
References 244 publications
12
278
2
21
Order By: Relevance
“…Chandon and Wansink illustrated how food marketing could negatively influence food choices and intake [29]. More specifically, interesting findings from Cavanagh and colleagues clearly demonstrate how powerful brands can be [37, 38•].…”
Section: Branding Perceived Healthiness Of Food and Food Intakementioning
confidence: 99%
See 1 more Smart Citation
“…Chandon and Wansink illustrated how food marketing could negatively influence food choices and intake [29]. More specifically, interesting findings from Cavanagh and colleagues clearly demonstrate how powerful brands can be [37, 38•].…”
Section: Branding Perceived Healthiness Of Food and Food Intakementioning
confidence: 99%
“…As described by Chandon and Wansink, food marketing that includes branding and food claims (in addition to food pricing strategies) can bias food consumption [29].…”
Section: Influence Of Cognitive Factors: Theoretical Backgroundmentioning
confidence: 99%
“…With increasing rates of obesity (Brownell and Horgen 2004;Chandon and Wansink 2012;Hill and Peters 1998) and childhood obesity (Hedley et al 2004;Troiano and Flegal 1998; though see Ogden et al 2014), understanding how to help children eat healthier is crucial (Birch 1999), especially from a young age (Cunningham, Kramer, and Narayan 2014). Prior research suggested several interventions, including increasing the accessibility of certain food items (Hearn et al, 1998;Just and Wansink 2009;Reicks et al 2012) or using appropriate role models (Birch 1980).…”
Section: Marketing Implicationsmentioning
confidence: 99%
“…Our research responds to the recent call to study large-scale consumer 26 transaction data (Griffith and O'Connell, 2009) from sample groups other than those consisting solely of North American undergraduate students (Chandon and Wansink, 2012).…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…One important feature of NB products is that only when recognized nutrient ingredient changes have been applied can a nutrition claim be made on food packaging due to severe scrutiny of public policymakers (Chandon and Wansink, 2012). For example, a claim of "low in fat" can only be used on product packaging when the product contains 3 grams or less of fat per 100 grams of solids, or 1.5 grams or less of fat per 100 ml for liquids (European Commission, 2006).…”
Section: Demand Patterns For Nb and Nnbmentioning
confidence: 99%